Diversivikasi Makanan dari Tanaman Singkong sebagai Upaya Pemberdayaan Perempuan Desa Ngrumpeng Kabupaten Grobogan Propinsi Jawa Tengah - Nuvitalia, Duwi; Sugiyanti, Sugiyanti; Endahwuri, Dhian (Pelita: Jurnal Pengabdian kepada Masyarakat, 2023)
The aim of the service activities in the PKK social gathering group "Nusa Indah dan Teratai" is to help solve the problems faced by partners. These include: 1) arisan group members will be able to create jobs independently, 2) foster an entrepreneurial spirit, and 3) increase the standard of living of arisan group members. This social gathering group consists of farmers and housewives who need additional incentives/income to meet household needs. The community as partners owns agricultural land, part of which is used for cassava plants. The cassava plant that has not yet been utilized for processed food has become an opportunity for the production of new snacks as an effort to empower housewives. Processed products include cassava chips, cassava leaf chips, cassava leaf jerky and also cassava cheese. After production activities, marketing is carried out in the Ngrumpeng village area, Putatsari Grobogan and also in the Semarang area. The results of diversifying cassava plants into snacks can empower women as housewives and increase income.